MEMAHAMI PERDA USUL INISIATIF DPRD DAN IMPLEMENTASINYA - Hidayat Rahman Hidayat Rahman (NIAGARA Scientific Journal, 2016)
This study aimed to analyze the implementation of the regulations proposed Regional initiatives Regional representatives Council Pandeglang District and its impact on the development process in the area.The methodology used in this study based on the analysis of qualitative models using effective causal analysis. The sourcesof information used in this study is the local regulations Pandeglang district government and local egulation initiative proposal legislature. Research carried out at the secretariat legislature Pandeglang district. Results the analysis against the hypothesis of the study shaw that there is an imbalance between local laws and regulations for local government initiatives legislature and its would be very disruptive to the process of development in Pandeglang district